Algorithm and Experimental Study of Circular Omnidirectional Focused Wave Synthesis for Extreme Wave Simulation - NI Yiping; WANG Tianyi; WANG Lei; LIN Jun; CHEN Jun; GUO Zebin (Renmin Zhujiang)
To reproduce extreme focused waves,based on the traditional two-dimensional double superposition focusing method,the spectral peak frequency,frequency band and wave amplitude distribution method have been improved,and a circular omnidirectional focused wave synthesis algorithm has been innovatively developed.The algorithm achieves the simulation of extreme focused waves and graphic focused waves,such as single-peaked focused waves,double-peaked focused waves,eccentric focused waves,rotating focused waves,and D-shaped focused waves.It is also capable to accurately control the focal position,height,diameter,verticality and other wave forms.Moreover,it can simulate strong nonlinear waves such as generating up jets with a height of up to 10 m and an impulse velocity of 13.8 m/s.In addition,the algorithm has the ability to simulate conventional waveforms,including rotating waves,standing waves and other regular waves,to fulfill the demand of traditional wave tests.